(untitled) (European Bison Conservation Newsletter, 2012)
The prevalence of antibodies to Neospora caninum was examined in European bison (Bison bonasus bonasus L.) eliminated at Białowiez˙a, Poland in 2010–2012. Sera of 45 European bison selected for elimination, of different ages and sexes, were tested for N. caninum antibodies using the ELISA test. Positive antibody responses were found in 5 males (prevalence 11.1 %). Our results confirm and indicate the presence of N. caninum in the European bison living in Białowiez˙a and further studies will be continued.